A rare case of giant GIST: a case report and review of literature - Muthukumarasamy, Thiruvarul; Ravikumar, Sumathi; Kumar, Vijay; ., Venkatraman (International Surgery Journal, 2024)
Gastrointestinal stromal tumors are very rare tumors that constitute less than 1 percent of entire tumors of GIT. The case reported here is a 60 years male who came with complaints of mass in the abdomen and constipation. On examination, he had guarding. Radiological evaluation revealed a heterogenous mass behind the lesser sac displacing the solid organs posteriorly. And hence we proceeded with total gastrectomy with esophago-jejunostomy. Histopathological examination revealed GIST arising from stomach which was positive for CD34 and C-KIT. Post-surgery patient was started on adjuvant imatinib therapy.